Simultaneous assay of segesterone acetate (Nestorone®), estradiol, progesterone, and estrone in human serum by LC-MS/MS - Erikson, David W. (Contraception, 2020)
OBJECTIVE –: To develop a method to simultaneously quantify the synthetic contraceptive progestin segesterone acetate (Nestorone®, NES) and the endogenous steroid hormones estradiol (E2), progesterone (P4), and estrone (E1) in human serum samples by liquid chromatography-tandem mass spectrometry (LC-MS/MS). STUDY DESIGN –: We analyzed 615 serum samples collected from 67 reproductive-age women actively using a contraceptive vaginal ring (CVR) designed to release NES (200 mcg/d) and E2 (75–200 mcg/d). Samples were taken prior to and up to 30 days after CVR insertion and analyzed for concentrations of NES, E2, P4, and E1 in human serum using a Shimadzu Nexera-LCMS-8050 LC-MS/MS platform. Precision, accuracy, and sensitivity for all analytes were determined across multiple assays. RESULTS –: The assay ranges for NES, E2, P4, and E1 in this analytical method were 10 pg/mL to 10 ng/mL with a lower limit of quantification of 10 pg/mL for all targets. Assay precisions were less than or equal to 14.5% and accuracies ranged from 87.0% – 110.8%. When applied to the 615 clinical samples, 550 samples had quantifiable concentrations of NES (value range 0.014 ng/mL – 1471 ng/mL). Similarly, 595 samples had quantifiable concentrations of E2 (0.010 ng/mL – 0.312 ng/mL), 596 samples had quantifiable concentrations of P4 (0.010 ng/mL – 5.791 ng/mL), and 609 samples had quantifiable concentrations of E1 (0.010 ng/mL – 0.416 ng/mL). CONCLUSIONS –: The LC-MS/MS platform results in a robust, accurate, and sensitive method for the simultaneous quantification of NES and endogenous steroid hormones in human serum. IMPLICATIONS –: The analytical method described allows for the simultaneous quantification of NES and endogenous steroids and can be used to monitor NES concentrations during clinical trials and subject adherence to treatment with NES.